Problematika Pembelajaran Fiqih pada Era Digital di MTS Nurul Islam 2 Boyolali - Amara Desinta; Dhina Suciyani; Nur Zaidi Salim (ARZUSIN, 2025)
The development of digital technology requires fiqh instruction to adapt to the characteristics of 21st-century learning; however, the reality in madrasah shows that the use of technology in fiqh learning has not been optimal. This study aimed to describe the implementation of fiqh instruction at MTs Nurul Islam 2 Boyolali in the digital era and to identify the obstacles encountered in applying instructional technology. A descriptive qualitative approach was employed, with data collected through observation and interviews with fiqh teachers and madrasah administrators, and subsequently analyzed descriptively. The findings indicate that fiqh learning is still dominated by conventional methods due to low levels of teachers’ digital competence and limited digital learning infrastructure. This situation results in low levels of active student engagement and suboptimal development of students’ digital literacy. The novelty of this study lies in its mapping of the interrelationship between teachers’ digital competence, infrastructure readiness, and the utilization of students’ potential as a digital generation in the context of fiqh instruction in madrasah. These findings highlight the importance of enhancing teachers’ digital competence and strengthening technology-based learning support systems in madrasah so that fiqh instruction becomes more relevant to the demands of the digital era.